2011
DOI: 10.1111/j.1365-2648.2010.05585.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of health‐promoting self‐care in people living with rheumatic diseases

Abstract: 1. I appreciate that English is not your first language. However, the English language and expression used in this paper is poor or incorrect in many places throughout. As the reviewer states this makes it hard for the reader to read and understand what your study is about. Publishers will not publish papers that do not have acceptable English. Can I suggest that you check throughout the paper that the English syntax, grammar, spelling, expression and meaning are clear and correct. On the JAN website guide to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
3
13
0
5
Order By: Relevance
“…The results from a study (Arvidsson et al 2011b) also confirmed the results about the important starting points from the focus-group interview. Following starting points which were linked to self-care when people with rheumatic diseases had chronic musculoskeletal pain, sleep disturbances and fatigue were determined in the curriculum: self-awareness and self-confidence, relationships to other, stress and relaxation, physical activity and rest, medicines and herbal remedies, tobacco and alcohol and food and drink.…”
Section: Interventionsupporting
confidence: 66%
“…The results from a study (Arvidsson et al 2011b) also confirmed the results about the important starting points from the focus-group interview. Following starting points which were linked to self-care when people with rheumatic diseases had chronic musculoskeletal pain, sleep disturbances and fatigue were determined in the curriculum: self-awareness and self-confidence, relationships to other, stress and relaxation, physical activity and rest, medicines and herbal remedies, tobacco and alcohol and food and drink.…”
Section: Interventionsupporting
confidence: 66%
“…Through the selfcare, Swedish chronic patients were ready to understand and respond to the signals their bodies sent out as a result of their illness. 44 After PR, the participants from our review avoided emergency attention due to a better understanding of COPD and the strategies to cope with the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of the PR described here positively influenced the selfmanagement of COPD patients. A qualitative study in Sweden with 12 people with rheumatic diseases 44 revealed the phenomenon of health-promoting selfcare as a 'way of life.' Similarly, PR, which also provides self-care among other benefits to people with chronic lung disease, 8,9,13,14 was recognized as a new 'way of life' by COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Las intervenciones educativas y actividades orientadas al auto-cuidado mejoran la calidad de vida de los pacientes con fibromialgia, los ayudan a conocerse mejor a sí mismos y a desarrollar ciertas capacidades necesarias para el afrontamiento de la enfermedad, como la de elegir, la de actuar por sí mismos o la de negociar (4,18,25,40) ; los profesionales sanitarios deben comprender la importancia de la esperanza en la experiencia de una enfermedad crónica ya que tiene un poder significativo en ayudar a las personas a entender su potencial durante todo su proceso (38,40,41) .…”
Section: Nº 35 Julio 2014 Página 280unclassified
“…La frustración derivada de la incomprensión domina en todos ellos por lo que prefieren no compartir sus experiencias con personas que no padezcan su enfermedad (5,10,14,26,37) . Los pacientes informan trastornos en las relaciones con familiares y amigos, aislamiento social, reducción de las actividades de la vida diaria y de ocio, evitan la actividad física y la pérdida de la carrera profesional (17,20,32,42) Desean establecer un equilibrio entre el deseo de permanecer independientes el mayor tiempo posible y la necesidad de apoyo por parte de los miembros de la familia y amigos (19,23,28,36,39,41) .…”
Section: Vivencia De La Enfermedadunclassified